1985
DOI: 10.1139/b85-304
|View full text |Cite
|
Sign up to set email alerts
|

Types of Florin rings, distributional patterns of epicuticular wax, and their relationships in the genus Pinus

Abstract: The shape of Florin rings and the distributional patterns of epicuticular wax of 51 species, including three varieties, in the genus Pinus were observed and classified with a scanning electron microscope. Six types of Florin rings and three types of wax distribution were observed. Florin ring structures and wax distribution correspond to subgenera. The restriction of the epicuticular waxes to the needle surface on which stomatal complexes occur suggests that the wax originates in association with the stomatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 7 publications
3
37
0
Order By: Relevance
“…The features of the stoma and cuticle structure observed were those generally used in descriptions of Finns subgenus Pinus (Trautmann, 1953;Mirov, 1967;Esau, 1982;Yoshie and Sakai, 1985; .<f fi .r e. Hansen, 1995;Farjon and Styles, 1997;Sweeney, 2003). The present study, however, identified significant differences among some of these variables that allow P. sylvestris and P. uncinata to be distinguished.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The features of the stoma and cuticle structure observed were those generally used in descriptions of Finns subgenus Pinus (Trautmann, 1953;Mirov, 1967;Esau, 1982;Yoshie and Sakai, 1985; .<f fi .r e. Hansen, 1995;Farjon and Styles, 1997;Sweeney, 2003). The present study, however, identified significant differences among some of these variables that allow P. sylvestris and P. uncinata to be distinguished.…”
Section: Discussionsupporting
confidence: 59%
“…Later studies have emphasized the taxonomic importance of this ring. Six different types have been identified; four of them occur in the subgenus Pinus, of which one is seen in P. sylvestris (Yoshie and Sakai, 1985;Farjon and Styles, 1997;Kim et al, 1999;Whang et al, 2001Whang et al, , 2004.…”
Section: Characteristics Of the Cuticlementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of conifer needles, the extent of development of epicuticular waxes depends on species (e.g., Whang et al, 2004), and their distribution on the leaf surface also varies among species (e.g., Burkhardt et al, 1995;Yoshie and Sakai, 1985).…”
Section: Epicuticular Waxmentioning
confidence: 99%
“…The stomata of many gymnosperms [9] and a few angiosperms appear to be partially blocked by filamentous waxes [10]. In the genus Pinus, the stomatal Florin ring and the stomata lantechamber [11] are covered with tubular epicuticular waxes, and this structural wax distribution reaches surrounding areas in the stomatal rows. These waxy plugs occlude the entrance of stomata, particularly in conifers [12] [13].…”
Section: Introductionmentioning
confidence: 99%